2015
DOI: 10.1039/c4sm01855a
|View full text |Cite
|
Sign up to set email alerts
|

Interlayer structure and self-healing in suspensions of brush-stabilized nanoplatelets with smectic order

Abstract: We have investigated the rheology of an uncured epoxy fluid containing high aspect ratio (length/thickness ≈ 160) α-zirconium phosphate (ZrP) nanoplatelets with smectic order. The nanoplatelets were exfoliated into monocrystalline sheets with uniform thickness using a monoamine-terminated oligomer. The oligomers were densely grafted to the plate surfaces and behave as a molecular brush. Suspensions containing ∼ 2 vol.% ZrP and above show liquid crystalline order with scattering peaks characteristic of a smecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 109 publications
(169 reference statements)
0
14
0
Order By: Relevance
“…Accordingly, the stabilization of nano-platelets with polymer brushes and their exfoliation into solvent-borne, lyotropic smectic phases 1517 has been used for the formulation of organic coatings via the addition of molecularly dissolved monomers and polymers 1721 . Such coatings have been proposed for anti-corrosive 6,22 and anti-scratch 23 applications.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the stabilization of nano-platelets with polymer brushes and their exfoliation into solvent-borne, lyotropic smectic phases 1517 has been used for the formulation of organic coatings via the addition of molecularly dissolved monomers and polymers 1721 . Such coatings have been proposed for anti-corrosive 6,22 and anti-scratch 23 applications.…”
Section: Introductionmentioning
confidence: 99%
“…These residues might be attributed to the deterioration of the resin. Amine-intercalated α-ZrP can act as latent thermal initiators [17,18] and the blocking residues of α-ZrP can act as additives for reinforcement of resins [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Polyetheramine and TBA are surfactants well‐known as good exfoliating agents for ZrP . We investigated the use of mixtures of low‐molecular‐weight surfactants to achieve our goal of significant reductions of CTE with minimal drop of T g .…”
Section: Resultsmentioning
confidence: 99%
“…An epoxy monomer plus hardener are then added to this dispersion, and the solvent is removed. We have shown that a long‐range order smectic structure is produced, which is maintained after cure . Although the polyetheramine works well as an exfoliating agent, it causes a substantial T g drop in comparison with the neat resin.…”
Section: Introductionmentioning
confidence: 99%